1981
DOI: 10.1128/aem.42.4.641-648.1981
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenicity testing of some commonly used dyes

Abstract: Seventeen commonly used dyes and 16 of their metabolites or derivatives were tested in the Salmonella-mammalian microsome mutagenicity test. Mutagens active with and without added Aroclor-induced rat liver microsome preparations (S9) were 3-aminopyrene, lithol red, methylene blue (USP), methyl yellow, neutral red, and phenol red. Those mutagenic only with S9 activation were 4-aminopyrazolone, 2,4-dimethylaniline, N,N-dirnethyl-p-phenylenediamine, methyl red, and 4-phenyl-azo-1-naphthylamine. Orange II was muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
70
0
7

Year Published

1988
1988
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(78 citation statements)
references
References 12 publications
1
70
0
7
Order By: Relevance
“…The investigators assumed impurities of the dye sample to be responsible for the weak positive result in the Ames test. The metabolites sulfanilic acid and 1 -amino-2-naphthol were also found to be Ames-negative [Chung et al, 1981;Garner and Nutman, 19771. No information on the mutagenicity of 1 -amino-2-naphthol-6-sulfonic acid could be obtained from the literature.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The investigators assumed impurities of the dye sample to be responsible for the weak positive result in the Ames test. The metabolites sulfanilic acid and 1 -amino-2-naphthol were also found to be Ames-negative [Chung et al, 1981;Garner and Nutman, 19771. No information on the mutagenicity of 1 -amino-2-naphthol-6-sulfonic acid could be obtained from the literature.…”
Section: Introductionmentioning
confidence: 98%
“…The same applies to Orange I1 [for reviews, see Combes and Haveland-Smith, 1982;Chung, 19831, with one exception. Chung et al [1981] found Orange I1 to be weakly mutagenic at high concentrations without metabolic activation; the addition of liver microsomes quenched this effect. The investigators assumed impurities of the dye sample to be responsible for the weak positive result in the Ames test.…”
Section: Introductionmentioning
confidence: 98%
“…The Panel therefore notes that a final conclusion from negative Ames test results obtained under standard conditions cannot be drawn. The Amaranth metabolites 1-amino-4-naphthalene sulphonic acid (naphthionic acid) and 2-naphthol-3,6disulphonic acid, sodium salt (R-amino salt) were however also judged to be non-mutagenic (Chung et al, 1981).…”
Section: Genotoxicitymentioning
confidence: 99%
“…These complex structures result in highly intense colors and resistance to biodegradation (O'Neill et al, 2000;Rajaguru, Kalaiselvi, Palanivel, & Subburam, 2000). However, many studies have indicated that MO is hazardous to both living organisms and ecological systems (Brown & Dietrich, 1983;Chung, Fulk, & Andrews, 1981). Therefore, the need for the decolorization of dye wastewater has received increasing attention to improve environmental protection.…”
Section: Introductionmentioning
confidence: 99%